Pengaruh Latihan On Elbow Vertical Skapular Push Up Pada Abnormal Posisi Skapula - Yuda Kristiawan; Nurul Halimah; Puspo Wardoyo; Angria Pradita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: to identify effect of exercise on elbow vertical scapular push up on abnormal scapular position.Methods: This research method used is a quasi-experimental design with a single group pre and post test. The subject is a patient with shoulder complaints in an independent physiotherapy practice, the research time is September until October 2021.Results: With the hypothesis if the p-value <0.05, then H0 is rejected and H1 is accepted. This means that there is an effect of changes in the position of the scapula in giving the On Elbow Vertical Scapular Push up exercise technique.Conclusion: The specific form of exercise On Elbow vertical scapular push up shows optimal results, this can be seen in changes/improvements in the position of the scapula.